Does International Publishing Still Matter for China’s Social Sciences Scholars? - Zha, Qiang (International Higher Education, 2024)
This article argues that the recent changes in China’s academic appraisal promote domestic publishing in social sciences, while the current stress on ideological correctness ushers in new barriers for China’s social sciences scholars to publish in international journals. As such, more and more of China’s social sciences scholars would choose to downplay or give up international publishing in the face of such changes and challenges.